Influence of family education style on psychological distance between family members - Третьякова, Тетяна Миколаївна; Третьякова, Т. М.; Третьякова, Татьяна Николаевна; Tretiakova, Tetiana M.; Лазор, Катерина Петрівна; Лазор, К. П.; Лазор, Екатерина Петровна; Lazor, Kateryna P.; Короход, Ясміна Джанівна; Короход, Я. Д.; Короход, Ясмина Джановна; Korokhod, Yasmina D.; et al. (Universidad del Zulia, 2019)
The purpose of this study is to determine the dependence of the length of psychological distance on the style of family education. To achieve the goal, the following methods were used: 1. The method of measuring psychological distance; 2. The sovereignty of psychological space questionnaire 3. Test - questionnaire of parental attitudes towards children (ORO). As a result, the educational impact is a necessary element in the formation of the personality of the adolescent. In conclusion, targeted parental education will help the parents correct their behavior with a teenager.

Метою цього дослідження є визначення залежності тривалості психологічної дистанції від стилю сімейного виховання. Для досягнення мети використовувались наступні методи: 1. Метод вимірювання психологічної дистанції; 2. Анкета суверенітету психологічного простору 3. Тест - анкета ставлення батьків до дітей (ОРО). Як результат, виховний вплив є невід'ємним елементом формування особистості підлітка. На закінчення, цілеспрямована батьківська освіта допоможе батькам виправити свою поведінку з підлітком.

Цель исследования - определить зависимость длительности психологической дистанции от стиля семейного воспитания. Для достижения цели использовались следующие методы: 1. Метод измерения психологической дистанции; 2. Анкета суверенитета психологического пространства 3. Тест - анкета родительского отношения к детям (ОРО). В результате влияние воспитания является неотъемлемым элементом в формировании личности подростка. В заключение, целевое обучение родителей поможет родителям исправить свое поведение с подростком.
Tretiakova T. N. Influence of Family Education Style on Psychological Distance between Family Members / T. N. Tretiakova, K. P. Lazor, Y. D. Korokhod, I. I. Ignatieva // Opción: Revista de Ciencias Humanas y Sociales. - Año 35, Especial No. 23. – Universidad del Zulia, 2019. – Р. 671-686.
Keywords: Psychological; Distance; Parenting; Style; Adolescence; психологічний; дистанція; виховання; стиль; підлітковий вік; психологический; дистанция; воспитание; стиль; подростковый возраст; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology